Aging of a Vanadium Precursor Solution: Influencing Material Properties and Photoelectrochemical Water Oxidation Performance of Solution‐Processed BiVO4 Photoanodes. (9th January 2019) - Byun, Segi; Jung, Gihun; Shi, Yuanyuan; Lanza, Mario; Shin, Byungha
Abstract: Metal–organic decomposition is an easy way to fabricate BiVO4 (BVO) photoanodes; however, it often experiences a reproducibility issue. Here, the aging duration of a vanadium precursor solution, vanadyl acetylacetonate in methanol, is identified as a factor that profoundly affects reproducibility. Substantial changes in structural, optical, and electrical properties of BVO films are observed upon varying aging time of vanadium precursor solutions, which subsequently impacts photoelectrochemical (PEC) water oxidation and sulfite oxidation reactions. With the optimum number of aging days (3 d), some deficiency of oxygen is observed, which is accompanied by an increase in carrier concentration and a reduced charge transfer resistance in the PEC device, which produces the highest PEC performance that is comparable to the state‐of‐the‐art undoped BVO photoanodes. The findings point to the importance of understanding solution chemistry and demonstrate that utilization of the understanding of fine adjustment of the composition of BVO films can produce highly reproducible and efficient BiVO4 photoanodes. Abstract : Highly efficient BiVO4 ‐based photoanodes are successfully created through a modified metal–organic decomposition protocol, which considers the solution aging effect of the vanadium precursor VO(acac)2 in methanol. The aging of the precursor solution occurs during ambient storage, which results in changes in the composition and donor density of BiVO4 . These changes produce an excellent photoelectrochemical water oxidation performance.